Upaya Pengasuh Dalam Mencegah Bullying Atau Kekerasan Antar Santri di Pondok Pesantren Darul Falah Purwoharjo - Al-Fatih, Muhammad Iqbal; Irawan, Vaesol Wahyu Eka; Indarsih , Fajar (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
This research aims to determine: (1) Violence that occurs at the Darul Falah Banyuwangi Islamic boarding school. (2) The efforts of Islamic religious education teachers in preventing violence between students at the Darul Falah Banyuwangi Islamic boarding school. This role is so that teachers can prevent violence through learning and activities in Islamic boarding schools. This type of research is qualitative using a descriptive approach. The subjects of this research were Islamic Religious Education Teachers and students of the Darul Falah Bnayuwangi Islamic Boarding School. Data collection techniques in this research used observation, interviews and documentation. Checking the validity of the data used triangulation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The results of the research show that (1) there are 2 forms of violence that occur at the Darul Falah Banyuwangi Islamic boarding school, namely: verbal violence and physical violence (2) The efforts of caregivers in preventing violence have played a good role and the efforts made are sufficient to meet the standardization of caregivers' efforts in preventing violence. , namely through teachers as teachers, mentors, class leaders, learning environment regulators, supervisors, motivators and evaluators. (3) The inhibiting factors for teachers or caregivers in preventing violence between students are inadequate boarding school facilities and infrastructure, a poor home environment and the most prominent is students who are less active, while the supporting factors are the role of parents and the teacher's educational background. good and what stands out most is the boarding school environment which has a positive impact as well as a sufficient portion of the curriculum in the field of religion